A cross-country comparison of malaria policy as a premise for contextualized appropriation of foreign aid in global health - Jezek, Tomas; Bamodu, Oluwaseun Adebayo (Health research policy and systems, 2021)
BACKGROUND: Foreign aid continues to play an essential role in health sector development in low-resource countries, particularly in terms of providing a vital portion of their health expenditures. However, the relationship between foreign aid allocation and malaria policy formulation and/or implementation among state aid recipients remains unknown. METHODS: Publicly available data were collected with the country as observational unit to set up the conceptual framework. The quality and strength of relationships between socioeconomic, environmental and institutional parameters were estimated by Pearson and polychoric correlations. A correlation matrix was explored by factor analysis. RESULTS: The first policy index captured policy variation related to malaria burden and development assistance. Funding per capita from all international agencies was correlated with malaria burden, whereas governmental funding for national malaria programmes per capita was not. The second policy index captured variation beyond malaria endemicity and country size. Variation was found to be related to international country risk instruments and funding from the United States Agency for International Development President's Malaria Initiative. CONCLUSIONS: Not all agencies involved in malaria policy allocate assistance in alignment with the gross domestic product and malaria burden. While the country size does not negatively impact malaria burden, it does account for greater development assistance per capita from selected international agencies. Novel policy indexes describe complex relationships between malaria policy, international foreign aid and socioeconomic parameters. Small countries have distinct environmental and sociopolitical properties.
Keywords: International agencies; International Cooperation; postup; malárie; Malaria; Healthcare economics and organizations; Global Health; Environmental health; Humans; celosvětové zdraví; Global health; Developing Countries; lidé; Health policy; Public health; mezinárodní spolupráce; Policy; rozvojové země